The perception of Chiang Rai’s Local Food Identity and Revisiting Intention of Thai Tourists - Saokham, Monsicha; Poomvichchuvech, Duangsiri; Srithong, Phuwanat; Boonpat, Sa-Ngiam; Boonpat, Orawan; Chootiraka, Munlita; Sitthikan, Sitthi (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to study (1) examine Thai tourists’ perceptions of Chiang Rai local food identity, (2) analyze the relationship between perceived local food identity and revisit intention, and (3) propose guidelines for developing perceptions of Chiang Rai local food identity in the Chiang Rai Municipality area, Chiang Rai Province. The sample was 398 Thai tourists visiting the Chiang Rai Municipality area and 15 key informants, including local food restaurant operators, relevant agency representatives, and academics. They were selected by stratified sampling for the quantitative sample and purposive sampling for the qualitative informants. The instrument for collecting data were a questionnaire and a semi-structured interview. Analysis data by Descriptive statistics Inferential statistics, cluster analysis, and Content Analysis. The research results were found as follows; 1. Thai tourists perceived Chiang Rai local food identity at a high level with an average score of 3.86, particularly in terms of taste, authenticity of local cuisine, and the use of natural local ingredients. 2. Perceived local food identity had a statistically significant relationship with revisit intention. Tourists could be classified into two distinct groups: those emphasizing taste and consumption frequency, and those focusing on cultural learning and online information channels. 3. The development of Chiang Rai local food perception should prioritize maintaining standards of taste, freshness, and food safety, alongside implementing differentiated marketing strategies tailored to specific tourist segments. This study demonstrates that local food identity acts as a strategic driver for revisit intentions. Furthermore, communicating cultural food identity via digital media specifically tailored for culture-oriented segments establishes a robust foundation for sustainable and targeted cultural marketing strategies.